A compact antenna for 4G mobile handset. Issue 9 (September 2014) - Jiu‐Sheng, Li; Di, Wu
ABSTRACT In this article, we propose a compact antenna using S‐shaped shorted strip and inverted L‐shaped shorted strip for 4G mobile handset. The measured impedance bandwidth defined by VSWR < 3 of 750 MHz (0.66–0.81 GHz), 2.6 GHz (2.25–2.85 GHz) and 3.5 GHz (3.28–3.97 GHz) are obtained, with the peak gains of 3.0/4.7/3.6 dBi. The presented antenna has a small size of only 21 × 15 mm2 and demonstrates omnidirectional radiation patterns, which show good performance for 4G application. The measured results are in agreement with the simulation. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:2199–2203, 2014